Integration of hepatic lipidomics and transcriptomics reveals dysregulation of lipid metabolism in a golden hamster model of visceral leishmaniasis - Yuan, Dongmei; Qin, Hanxiao; Yu, Zeying (Frontiers in Immunology, 2025)
Visceral leishmaniasis (VL), the most severe form of leishmaniasis, remains a significant public health concern that cannot be overlooked in underdeveloped regions. Studies suggest that lipids play a crucial role in the survival of Leishmania parasites in mammalian hosts. However, a comprehensive understanding of the characteristics and underlying mechanisms of lipid metabolism in VL hosts is lacking. In this study, we conducted lipidomic and transcriptomic analyses of liver tissues from VL golden hamsters at 12 weeks post-infection (WPI) and performed integrated analysis. Simultaneously, qPCR validation of several key regulatory enzymes was performed at the tissue level. The results revealed a decreased abundance of phospholipids such as phosphatidylethanolamine (PE) and phosphatidylcholine (PC) and an increased abundance of their metabolites, including lysophosphatidylcholine (LPC), lysophosphatidylethanolamine (LPE), lysophosphatidylserine (LPS), and platelet-activating factor (PAF). Conjoint pathway analysis revealed that glycerophospholipid (GPL) metabolism, arachidonic acid (AA) metabolism, glycerolipid metabolism, and linolenic acid metabolism were the pathways with relatively high proportions of common enrichment. In the GPL metabolism and AA metabolism pathways, the transcription levels of genes such as phospholipase A2 (PLA2) family enzymes, cyclooxygenase-2 (Cox-2), arachidonate 5-lipoxygenase (Alox5), and hematopoietic prostaglandin D synthase (Hpgds), all of which regulate phospholipid hydrolysis and lipid mediator production, were significantly increased. Additionally, we found that the expression of lysophosphatidylcholine acyltransferase 1/2 (Lpcat1/2), the enzyme regulating PC remodeling, was upregulated and that the levels of saturated PCs (PC30:0, PC32:0, and PC34:0) were simultaneously significantly increased simultaneously. These findings suggest that Leishmania infection may regulate PC remodeling in the host liver and increase membrane phospholipid metabolism, resulting in the production of a series of lipid mediators that participate in immune regulation; this could have a significant impact on the survival of Leishmania in the host and on the progression of the disease.